Lactate Suppresses Macrophage Pro-Inflammatory Response to LPS Stimulation by Inhibition of YAP and NF-κB Activation via GPR81-Mediated Signaling - Yang, Kun; Xu, Jingjing; Fan, Min; Tu, Fei; Wang, Xiaohui; Ha, Tuanzhu; Williams, David L.; Li, Chuanfu (Frontiers in Immunology, 2020)
Recent evidence from cancer research indicates that lactate exerts a suppressive effect on innate immune responses in cancer. This study investigated the mechanisms by which lactate suppresses macrophage pro-inflammatory responses. Macrophages [Raw 264.7 and bone marrow derived macrophages (BMDMs)] were treated with LPS in the presence or absence of lactate. Pro-inflammatory cytokines, NF-κB and YAP activation and nuclear translocation were examined. Our results show that lactate significantly attenuates LPS stimulated macrophage TNF-α and IL-6 production. Lactate also suppresses LPS stimulated macrophage NF-κB and YAP activation and nuclear translocation in macrophages. Interestingly, YAP activation and nuclear translocation are required for LPS stimulated macrophage NF-κB activation and TNFα production. Importantly, lactate suppressed YAP activation and nuclear translocation is mediated by GPR81 dependent AMKP and LATS activation which phosphorylates YAP, resulting in YAP inactivation. Finally, we demonstrated that LPS stimulation induces an interaction between YAP and NF-κB subunit p65, while lactate decreases the interaction of YAP and NF-κB, thus suppressing LPS induced pro-inflammatory cytokine production. Our study demonstrates that lactate exerts a previously unknown role in the suppression of macrophage pro-inflammatory cytokine production via GPR81 mediated YAP inactivation, resulting in disruption of YAP and NF-κB interaction and nuclear translocation in macrophages.